The space between - Thorpe, Kiki.; Christy, Jana (New York : Random House, 2013)
While wondering if she has a talent for animals, Lainey, along with her three friends and the fairies of Pixie Hollow, discovers a passage between Earth and Never Land.
"A Stepping Stone book."
Series at head of cover title.
"Disney."
609
Accelerated Reader
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Ability -- Juvenile fiction; Animals -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Ability -- Fiction; Animals -- Fiction